Legalization or Enforcement? Fiscal Justice and MSME Protection in Indonesia’s Thrifting Policy - Ibnususilo, Efendi; Shalihah, Fithriatus; Hariz, Hajar Salamah Salsabila; Barak, Ahmed Mohamed; Ezzerouali, Souad (Jambe Law Journal, 2026)
This article addresses the policy dilemma surrounding Indonesia’s prohibition on imported used clothing, which pits trade law enforcement and domestic textile protection against the socio-economic survival of thrifting merchants operating as MSMEs. It investigates whether taxing these activities can be justified when the underlying traded goods remain legally banned. While previous legal scholarship has treated trade restrictions, tax law, and MSME protection in a fragmented manner, this study establishes a novel, integrated research position by examining these intersecting regimes through a unified normative legal framework. Using a normative juridical method, the paper evaluates relevant laws, regulations, and tax court decisions through statutory, conceptual, and public policy approaches. The discussion demonstrates that direct taxation of prohibited imported goods creates severe normative ambiguity and fails to satisfy substantive fiscal justice. However, the study concludes that a "non-legitimate transitional scheme" is legally viable. This alternative policy separates the legal status of the goods from the business subjects, limiting taxation strictly to lawful domestic economic aspects while actively providing business conversion and structured MSME empowerment support.